The Binding Affinity of Small Molecules with Yam Tyrosinase (Catechol Oxidase): A Biophysical Study - Tabassum Mulla; Sushama Patil; Srinivas Sistla; Jyoti Jadhav (Biochemistry Research International)
Yam tyrosinase has become an economically essential enzyme due to its ease of purification and abundant availability of yam tubers. However, an efficient biochemical and biophysical characterization of yam tyrosinase has not been reported. In the present study, the interaction of yam (Amorphophallus paeoniifolius) tyrosinase was studied with molecules such as crocin (Crocus sativus), hydroquinone, and kojic acid. Surface plasmon resonance (SPR), fluorescence spectroscopy, and circular dichroism techniques were employed to determine the binding affinities and the changes in secondary and tertiary structures of yam tyrosinase in the presence of four relevant small molecules. Hydroquinone and crocin exhibited very low binding affinities of 0.24 M and 0.0017 M. Due to their apparent weak interactions, competition experiments were used to determine more precisely the binding affinities. Structure-function interrelationships can be correlated in great detail by this study, and the results can be compared with other available tyrosinases.